Identification of Resectable N2 in NSCLC: A Single Center Experience and Review of the SEER Database - Wang, Yan-qing; Liu, Xu-dong; Bai, Wen-liang; Li, Shan-qing (Frontiers in Oncology, 2021)
Background: Non-small cell lung carcinoma (NSCLC) with ipsilateral and/or subcarinal mediastinal lymphatic spread (N2) is a heterogeneous disease. The role of surgical resection in patients with N2 NSCLC remains controversial and no survival-based definition of “resectable N2” exists. The purpose of this study is to evaluate the factors that potentially affect the survival of N2 NSCLC patients who receive surgical resection and to define “resectable N2” based on the survival benefits. Methods: Data from the open Surveillance, Epidemiology, and End Results (SEER) database from the National Cancer Institute in the United States were used to construct a nomogram. Patients who received surgery between 2010 and 2015 for N2 NSCLC were included. Independent prognostic factors for survival identified through COX regression analysis were used to create the nomogram. The C-index, receiver operating characteristics (ROC) analyses, calibration curves, and risk stratification were used to evaluate the nomogram. The nomogram was also validated using data from 222 patients from Peking Union Medical College Hospital (PUMCH). Furthermore, lung cancer–related deaths were compared using competitive risk analysis. Results: In total, 4267 patients were included in the SEER cohort. Male gender, old age, high T stage and grade, adenosquamous and squamous cell carcinoma, lower lobe and overlapping lesions, extended lobe or bilobectomy and pneumonectomy, no chemotherapy, radiation before and after surgery, positive number of lymph nodes, and lymph node ratio (LNR) were identified as independent risk factors for non-survival. The nomogram was created using these parameters. The C-index was 0.665 (95% confidence interval (CI), 0.651-0.679) and 0.722 (95% CI, 0.620-0.824) in the SEER and PUMCH cohorts, respectively. The calibration curves showed satisfactory consistency between the predicted and actual survival status in both the SEER and PUMCH cohorts. Competitive risk analysis confirmed that the variables in the nomogram, except radiation, are risk factors for prognosis. Conclusions: “Resectable N2” should be assessed by a multidisciplinary team. The novel nomogram developed in this study may help with clinical decision-making for this patient population.